Mapping the Epidemic: A Macro and Micro Analysis of Opioid Abuse Trends and Clustering in U.S. States and Counties - Patel, Priya; Sharma, Rahul (Journal of Computer Science and Software Applications, 2022)
The United States is currently grappling with a widespread opioid abuse crisis, which poses significant detrimental impacts on both public health and key sectors of the national economy. This paper endeavors to pinpoint potential areas where opioid use is particularly prevalent. To this end, we have constructed a comprehensive macro model to examine the drug epidemic at both state and county levels. The state-level model generates the drug spread curve for each state, while the county-level model employs the k-means clustering method to categorize counties within each state. By scrutinizing the characteristics of the clustering centers, we identify regions that may have initiated the use of specific opioid drugs.